Politisk deltagelse under autoritær kontrol - ”Konsultativt demokrati” og overvåget offentlighed i Kina - Thøgersen, Stig (Slagmark - Tidsskrift for idéhistorie, 2018)
This article looks at policies implemented in China under the heading of ”consultative democracy”, and at how the Internet challenges authoritarian one-party rule. It argues that it is still difficult to see a distinct Chinese model of democratization emerge from these trends, but that the combination of social conflicts, quickly rising levels of education, better access to information and increased political participation through local elections makes the future trajectory of political reforms unpredictable.